2011
DOI: 10.1128/mcb.01009-10
|View full text |Cite|
|
Sign up to set email alerts
|

miR-206 and -486 Induce Myoblast Differentiation by Downregulating Pax7

Abstract: The Pax7 transcription factor is required for muscle satellite cell biogenesis and specification of the myogenic precursor lineage. Pax7 is expressed in proliferating myoblasts but is rapidly downregulated during differentiation. Here we report that miR-206 and -486 are induced during myoblast differentiation and downregulate Pax7 by directly targeting its 3 untranslated region (UTR). Expression of either of these microRNAs in myoblasts accelerates differentiation, whereas inhibition of these microRNAs causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
257
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(272 citation statements)
references
References 49 publications
13
257
2
Order By: Relevance
“…miR-206 has been well characterized in muscle cells, where it promotes skeletal muscle regeneration in response to injury (81)(82)(83). An in silico search for cancer-relevant influences of miR-206 identified regulation of MAPK signaling as a likely effector pathway with potential effects on RASA1 and SPRED1 (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…miR-206 has been well characterized in muscle cells, where it promotes skeletal muscle regeneration in response to injury (81)(82)(83). An in silico search for cancer-relevant influences of miR-206 identified regulation of MAPK signaling as a likely effector pathway with potential effects on RASA1 and SPRED1 (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the differentiation-related miRNAs, miR-206 has been demonstrated to play a crucial role in the process of cellular differentiation. Dey et al [25] showed that the differentiation and proliferation of myoblasts were modulated by miR-206 through its direct target, pax7. Inose et al [26] identified miR-206 as a key regulator of osteoblast differentiation, where it acts by inhibiting the expression of the connexin 43 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the myogenic differentiation route is favored by the loss of Pax7 and by Myog induction. As Pax7 expression is negatively regulated by microRNAs (miRNAs) 1, 206, and 486, which are themselves controlled by MyoD expression in myoblast differentiation (58,59), a quantification of these miRNAs should be conducted in our cell lines.…”
Section: Discussionmentioning
confidence: 99%